Shaped by the story: narrative theology, storytelling and Christian Religious Education - Belmonte, Angelo (British Journal of religious education, 2025)
The article is grounded on the basis that people are narrative beings and our identities are founded on stories that present a window for which we can view the world. It explores the significance of narrative theology, where Christian communities move away from the intellectual plane of credal statements, and closer to the way Christian faith first began and spread. As illustrated through his own narrative style Jesus used, storytelling can be used by religious educators as an effective teaching tool to connect with the hearts and minds of people. This paper argues then that story must be viewed as an essential element of Christian Religious Education because the task of the religious education teacher is to convey the divine story of God’s communion with humankind and the world. The challenge for Christian Religious Educators is to reclaim their role as storytellers and to revitalise the impact of story.